Madani Community and Criminal Action on Children's Online Prostitution in Social Media - Fransiska Novita Eleanora (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2019)
Rampant and rampant crime against children on social media, resulting in increasingly restless and worried every parent, especially trafficking child prostitution, and carried out using the internet media. This online prostitution also spreads the contents of child pornography, whether done by the perpetrators themselves, a group of people or even corporations. The aim is to find out how to deal with civil society in dealing with child crimes through online prostitution, the ways that civil society do in eradicating crimes or criminal acts that occur in the environment or civil society life so that they are always vigilant, cautious and not easily trapped in criminal acts or crimes that occur in social medial that is by using social media namely through the internet, or facebook, instagram and so forth. While the research method used is normative research that is by examining and processing theories or in existing concepts and regulations and even legislation that is considered relevant and related to this research, in this case cannot be separated by using books or literature which exists. The results of this finding are various mitigation efforts that can be carried out by civil society in responding to criminal acts related to online prostitution of children, namely by carrying out various measures which are also called preventive, repressive, persuasive, curative and rehabilitation, considered to be able to reduce prostitution crime. existing children on social media, accompanied by a mindset which is advanced modern and supervision from the community and law enforcement which exist.